2009
DOI: 10.1167/9.10.9
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of a novel cue for active control depends on control dynamics

Abstract: We investigated how the visual-motor system recruits a novel visual feedback cue for a manual control task. We presented conditions in which an arbitrary cue (color) was coupled with task-relevant feedback (position or velocity), and measured the effect of the novel cue on performance. Participants used a joystick to keep a moving horizontal line centered on a display under velocity or acceleration control dynamics. Participants normally rely primarily on line position feedback for velocity control and line ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…4. The duration of each trial was 95 s. Following previous studies on manual control (Li et al 2005(Li et al , 2006aLi WO et al 2009), all chosen frequencies for the vehicular heading and orientation perturbations went through an integer number of cycles in 90 s, and we added 5 s in each trial, such that we could skip the initial transient response at the beginning of the trial.…”
Section: Visual Stimuli and Controlmentioning
confidence: 99%
“…4. The duration of each trial was 95 s. Following previous studies on manual control (Li et al 2005(Li et al , 2006aLi WO et al 2009), all chosen frequencies for the vehicular heading and orientation perturbations went through an integer number of cycles in 90 s, and we added 5 s in each trial, such that we could skip the initial transient response at the beginning of the trial.…”
Section: Visual Stimuli and Controlmentioning
confidence: 99%
“…Learning can therefore be portrayed as the process by which individuals gradually change from less useful to more useful informational variables. This process has been observed with verbal estimates (Jacobs, Runeson, & Michaels, 2001;Michaels & de Vries, 1998;Runeson, Juslin, & Olsson, 2000;Withagen & Michaels, 2005), ballistic actions (Fajen & Devaney, 2006;Smith, Flach, Dittman, & Stanard, 2001), and actions that are not ballistic (Fajen, 2008a(Fajen, , 2008bLi, Saunders, & Li, 2009). Jacobs and Michaels (2007) proposed that informational variables can be portrayed as forming a continuous space, referred to as information space.…”
mentioning
confidence: 98%
“…actions that are not ballistic (Fajen, 2008a(Fajen, , 2008bLi, Saunders, & Li, 2009). Jacobs and Michaels (2007) proposed that informational variables can be portrayed as forming a continuous space, referred to as information space.…”
mentioning
confidence: 99%
“…It has also been shown that human operators can perform such a closed-loop visual motor control task under various controller dynamics [32], [33], [34]. Based on these findings, Li et al have developed a simple closed-loop visual motor control task that involves controlling a randomly moving visual target on the screen to evaluate how the visual system uses different sources of visual information for the control of target motion [35], [36], and how the recruitment of new visual information for visual motor control is affected by controller dynamics [37].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we used a simple closed-loop visual motor control task similar to that developed by Li et al [35], [36], [37] to evaluate the visual motor control abilities of HH patients. The goal was to compare the control performance of HH patients to that of a group of age-matched normally sighted participants to determine the extent to which the visual impairment in HH patients affects their ability to effectively use visual information for online control of a moving target.…”
Section: Introductionmentioning
confidence: 99%